Synthesis and Antimicrobial Activity of Pyrimidine Salts with Chloranilic and Picric Acids - C. Mallikarjunaswamy; D. G. Bhadregowda; L. Mallesha (Journal of Chemistry)
Pyrimidine salts such as 2-methyl-5-nitro-phenyl-(4-pyridin-3-yl-pyrimidin-2-yl)-amine (1) and 4-methyl-3-(4-pyridin-3-yl-pyrimidin-2-yl-amino)-phenyl-amine (2) with chloranilic and picric acids were synthesized, and their in vitro antibacterial and antifungal activities were evaluated. The synthesized compounds were characterized by elemental analyses, UV-visible, FT-IR, and 1H NMR spectral studies. Compound 2a exhibited good inhibition towards antimicrobial activity compared to the other compounds.